Análise dos tecidos moles no terço inferior da face de pacientes submetidos à cirurgia ortognática para avanço mandibular utilizando o programa Dolphin - Rocha Junior, Nelson Agnese da (2011)
Objective: Evaluate by cephalometric analysis of soft tissues (ACTM), the soft profile of the lower third of the face in patients who underwent mandibular advancement. To measure the soft tissue, lower lip, chin (Pog '), mentolabial and compare the soft tissue profile predictive software with the actual profile post-surgical treatment. To verify the accuracy of the Dolphin program 11.5 in the planning of mandibular advancement surgery Methods: We used cephalometric radiographs of 15 patients with Angle class II occlusion. All radiographs were digitized and entered into the Dolphin Imaging software and 16 soft tissue points and 22 points were marked facial skeleton, followed by the exact markings and Arnett MacLauglin analysis, aimed to assess the soft tissue profile of the lower face. Results: The results were evaluated and showed no statistically significant difference between the profile and profile predictive of the program post-surgical soft tissues real. Conclusion: These data show that the Dolphin software is an excellent tool for diagnosis and planning in cases of mandibular advancement.